2015
DOI: 10.1111/sji.12269
|View full text |Cite
|
Sign up to set email alerts
|

Cry1Ab Protein from Bacillus thuringiensis and MON810 cry1Ab‐transgenic Maize Exerts No Adjuvant Effect After Airway Exposure

Abstract: The genetically modified (GM) maize event MON810 has been inserted with a processed version of the transgene, cry1Ab, derived from the soil bacterium Bacillus thuringiensis (Bt) to express proteins with insecticidal properties. Such proteins may introduce new allergens and also act as adjuvants that promote allergic responses. While focus has been on safe consumption and hence the oral exposure to GM food and feed, little is known regarding inhalation of pollen and desiccated airborne plant material from GM cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…ovalbumin) was observed (Vázquez-Padrón et al 1999 ; González-González et al 2015 ; Moreno-Fierros et al 2015 ). In contrast, the adjuvant effect of Cry1Ab on ovalbumin was not observed in BALB/c mice after airway exposure to extracts of MON810 pollen/leaf or trypsinized Cry1Ab (Andreassen et al 2015b ). Thus, the issue of adjuvanticity seems to be related to the exposure conditions and, particularly, to the administered doses, although very little is known regarding the dose–response relationship to induce this effect.…”
Section: Discussionmentioning
confidence: 99%
“…ovalbumin) was observed (Vázquez-Padrón et al 1999 ; González-González et al 2015 ; Moreno-Fierros et al 2015 ). In contrast, the adjuvant effect of Cry1Ab on ovalbumin was not observed in BALB/c mice after airway exposure to extracts of MON810 pollen/leaf or trypsinized Cry1Ab (Andreassen et al 2015b ). Thus, the issue of adjuvanticity seems to be related to the exposure conditions and, particularly, to the administered doses, although very little is known regarding the dose–response relationship to induce this effect.…”
Section: Discussionmentioning
confidence: 99%
“…The present study does not indicate adverse health effects of trypCry1Ab in terms of immunogenic, allergenic or adjuvant properties, however, there are several experimental limitations that should be considered. The Cry1Ab protein is expressed at low levels in plant material (6.92 and 612.51 ng/mg Cry1Ab in pollen and leaves, respectively, reported in Andreassen et al [ 21 ]), and methods for isolation/extraction of plant Cry1Ab protein in sufficient amounts for this study was not available. Therefore, a recombinant version was produced in the E. coli bacteria and subsequently trypsin digested to “mimic” the activated form expressed in the plants.…”
Section: Discussionmentioning
confidence: 99%
“…The structurally similar Cry1Ac protein has demonstrated adjuvant capacity in several studies [ 17 19 ]. To our knowledge, only three studies have investigated allergic adjuvant effects of Cry1Ab, reporting no [ 20 , 21 ] and possible [ 22 ] adjuvant capacity after exposure by airways installation, feeding and oral gavage, respectively. So far, no experimental studies have investigated whether Cry proteins have adjuvant properties in relation to clinical food allergy responses.…”
Section: Introductionmentioning
confidence: 99%
“…However, neither study demonstrated that these increased markers resulted in any clinical allergy in the mouse models. 43,44 The third study identified was a case series describing sensitization in subjects with known Brazil nut allergy (by skin testing, serum IgE testing, and western blotting) to GM soy through cross-recognition of a 2S albumin Brazil nut protein that had been genetically engineered into the soybeans to increase their nutritional value. However, none of these subjects with allergy to Brazil nut were challenged to the GM soy to demonstrate whether the sensitization had any clinical significance, although the investigators concluded that this demonstrated the potential for inadvertent allergen transfer through genetic modification.…”
Section: Studies Demonstrating Evidence Of Harmmentioning
confidence: 99%